Practical effects of pressure-transmitting media on neutron diffraction experiments using Paris–Edinburgh presses. Issue 3 (2nd July 2020) - Hattori, T.; Sano-Furukawa, A.; Machida, S.; Ohuchi, K.; Kira, H.; Abe, J.; Funakoshi, K.
ABSTRACT: To understand the practical effects of pressure-transmitting media (PTM) on neutron diffraction using Paris–Edinburgh presses, diffraction patterns of MgO were collected to approximately 20 GPa using PTMs of Pb, AgCl, 4:1 methanol–ethanol (ME) mixture with and without heating, N2, and Ar. Hydrostaticity in the sample chamber estimated from the MgO 220 peak width improves in the order of Pb, AgCl, Ar, ME mixture, N2, and the heated ME mixture. Unlike previous results using diamond anvil cells, the unheated ME mixture is superior to Ar even after freezing, probably due to the cup on the anvil face. Considering these results and the sizable coherent scattering of Ne, which would show good hydrostaticity, we conclude that the ME mixture (preferably the heated one) is the best PTM in neutron experiments up to 20 GPa, while Ar can be substituted when a sample is reactive to alcohols.